PENINGKATAN MUTU PENDIDIKAN MELALUI MANAJEMEN PESERTA DIDIK - Umam, Muhammad Khoirul (Jurnal al Hikmah, 2018)
The purpose of writing this article discusses about improving the quality of education through students is one of the important components in the education system, in the world of education students are the main raw material in the process of scientific change of knowledge. Learning can be interpreted as components that are interconnected with each other. These components include goals, materials, methods, and evaluations. The four components of learning must be carefully considered by the teacher in selecting or determining the approach and learning model. Doing activities in implementing them, recognizing many terms to describe the way the teacher will do teaching. Now there are so many kinds of learning strategies or methods that aim to improve the quality of learning so that it becomes better